184. Seven vs. 14 Days Treatment Duration for Afebrile Men with Urinary Tract Infections; A Randomized Clinical Trial. (31st December 2020) - Drekonja, Dimitri; Johnson, James R; Carla, Amundson; Kuskowski, Michael; Trautner, Barbara
Abstract: Background: Trials show that shorter-duration therapy is effective for many infectious diseases, but the optimal duration for UTI in men is unknown. Observational data suggests shorter-duration performs as well as longer-duration therapy, but trial data shows men with febrile UTI (a small but important subset of patients) do worse with 7 vs. 14 days of therapy. We performed a randomized controlled trial of afebrile men with UTI to determine whether 7 days of treatment was non-inferior to 14 days. Methods: Men with symptomatic UTI at 2 VA hospitals were enrolled. Inclusion criteria included male gender, outpatient treatment, prescribed 7 to 14 days of ciprofloxacin or trimethoprim/sulfamethoxazole, and new onset of at least 1 of: dysuria, frequency, urgency, hematuria, costovertebral angle tenderness, and perineal, flank, or suprapubic pain. Exclusion criteria included UTI treatment in the past 14 days, symptoms due to a non-UTI diagnosis, and inadequate empiric treatment. Enrolled subjects took their clinically-prescribed medications days 1–7, then study medication days 8–14. Study medications were placebo or the originally prescribed antimicrobial, different in appearance from the original medication. The primary outcome was percentage of subjects with symptom resolution 14 days after completion of active therapy. Secondary outcomes included recurrence of UTI and adverse events. A pre-specified minimally clinically significant difference of 10% was selected, with a P value of 0.05 considered to be significant. Primary analysis was per-protocol; intention-to-treat performed as secondary analysis. Results: Enrollment totaled 273, with 272 randomized to 7 (n = 136) vs. 14 (n = 136) days of antimicrobials. Mean age was 67.8 (SD 11.6), with a mean Charlson comorbidity index of 1.3 (SD 1.6). Overall, 254 subjects were in the per-protocol analysis. Symptom resolution occurred in 122 of 131 (93.1%) subjects receiving 7 days treatment, and 111 of 123 (90.2%) receiving 14 days (difference 2.9%, 95% CI -4.7 to 10.5% P = .50), confirming non-inferiority. Intention-to-treat analysis (n = 272) showed similar results. Conclusion: Treatment with 7 days of antimicrobials was non-inferior to 14 days for symptom resolution. Afebrile men with UTI should not be treated beyond 7 days. Disclosures: All Authors : No reported disclosures